2014
DOI: 10.1371/journal.pone.0108253
|View full text |Cite
|
Sign up to set email alerts
|

Optimizations of SiRNA Design for the Activation of Gene Transcription by Targeting the TATA-Box Motif

Abstract: Small interfering RNAs (siRNAs) are widely used to repress gene expression by targeting mRNAs. Some reports reveal that siRNAs can also activate or inhibit gene expression through targeting the gene promoters. Our group has found that microRNAs (miRNAs) could activate gene transcription via interaction with the TATA-box motif in gene promoters. To investigate whether siRNA targeting the same region could upregulate the promoter activity, we test the activating efficiency of siRNAs targeting the TATA-box motif … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 86 publications
0
5
0
1
Order By: Relevance
“…Usually, acute exposure to environmental pollutant is more likely to cause changes in gene transcription levels rather than in DNA methylation levels; hence, we speculate that the decreased DNA methylation may be a negative feedback effect in response to over-inhibition of gene transcription to prevent further reductions in gene level (Marik et al, 2010). Besides DNA methylation, there are other epigenetic modifications which were involved in the gene transcriptional regulation such as intracellular circular RNA, microRNA, siRNA and histone modification, and chromatin remodeling (Borel et al, 2012;Fan et al, 2014;Li et al, 2015;Monga et al, 2011;Zhu et al, 2020), and those other modifications were not mentioned in this study.…”
Section: Discussionmentioning
confidence: 96%
“…Usually, acute exposure to environmental pollutant is more likely to cause changes in gene transcription levels rather than in DNA methylation levels; hence, we speculate that the decreased DNA methylation may be a negative feedback effect in response to over-inhibition of gene transcription to prevent further reductions in gene level (Marik et al, 2010). Besides DNA methylation, there are other epigenetic modifications which were involved in the gene transcriptional regulation such as intracellular circular RNA, microRNA, siRNA and histone modification, and chromatin remodeling (Borel et al, 2012;Fan et al, 2014;Li et al, 2015;Monga et al, 2011;Zhu et al, 2020), and those other modifications were not mentioned in this study.…”
Section: Discussionmentioning
confidence: 96%
“…It has been suggested that 200- to 1200-bp upstream of the TSS is the optimal targeting area ( 5 ) and actually, most of the known active saRNA target sites are located upstream of and no more than 1 kb from the TSS. Particularly, it has been proposed that saRNAs targeting sequences around the TSS or the TATA-box-centered region might have higher activation efficiency ( 6 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Fan et al designed and evaluated the potential of TATA-box-targeting small interfering RNAs (siRNAs) in the regulation of gene expression. They also identified four characteristics that contribute to the high efficiency of TATA-box-targeting activating siRNAs on IL-2 promoter activation: UA at the 3′ end of the antisense strand (23 nucleotides in length), which targets the center of TATA-box (~34 bp upstream the TSS), as well as 2′-OMe modified bases at the 3′ terminus of the antisense strand (31). In other recent studies, the same group revealed that a novel HIV-1-encoded miRNA, miR-H3, could target the TATA-box motif within HIV-1 5′ long terminal repeat (LTR) and enhance viral replication (32).…”
Section: Promoter Regulation By Mirnas Beyond Methylation and Acetylamentioning
confidence: 99%